THE INFLUENCE OF WORK-FAMILY CONFLICT AND REWARD ON JOB SATISFACTION AND JOB PERFORMANCE IN FOOTWEAR MANUFACTURE, TANGERANG - Williamarshall Malta; Justine Tanuwijaya (JWM (JURNAL WAWASAN MANAJEMEN), 2023)
This study aims to examine the effect of family-friendly policies and supervisor support on work-family conflict as well as the effect of work-family conflict and rewards on job satisfaction and job performance. This study uses a quantitative approach by using a questionnaire. Questionnaires were given to 93 respondents who are employees of the footwear manufacturing industry in Tangerang, Banten. Data analysis was performed using SEM-PLS. The results showed that there was a significant effect of supervisor support and reward on work-family conflict and job satisfaction as well as the effect of job satisfaction on job performance. The results imply that employee feel more satisfied with their work and increase their performance while conflict between their work and family can be decreased caused support from their leaders.